Soil moisture and micrometeorological differences across reference and thinned stands during extremes of precipitation, southern Cascade Range - Hardage, Kyle; Wheelock, Shawn J.; Gaffney, Rowan; O’Halloran, Theresa; Serpa, Benjamin; Grant, Gordon; Coppoletta, Michelle; Csank, Adam; Tague, Christina; Staudacher, Matthew; Tyler, Scott (Frontiers in Forests and Global Change, 2022)
Modern forest management often relies on thinning treatments to reduce fuels and mitigate the threat of catastrophic wildfire. Thinning has also been proposed as a means to increase downstream flows of water by reducing evapotranspiration. Concurrently, warming climates are causing many forests to transition from snow-dominated to rain-dominated, thereby reducing the storage of water later into the summer season. There are relatively few studies, however, that directly measure the hydrologic impacts of thinning treatments during and following snow-free winters for forests located within this transition zone. This work compares the below-canopy meteorological and subsurface hydrologic differences between two thinning prescriptions and an unaltered Control during periods of extreme drought and above-average precipitation (with little snow) at a coniferous forest site in the rain-snow transition zone of the southern Cascades, near the Sierra Nevada of California. Both thinning prescriptions had a modest and predictable impact on below-canopy meteorology, including lower nighttime minimum temperatures during the critical summer months and higher wind speeds. Relative to the Control, measurements in both thinning treatments demonstrated an impact on soil moisture storage, with delayed timing of annual soil moisture decline and increased minimum soil moisture storage by the end of summer. The onset of soil moisture depletion was strongly tied to the magnitude of the winter precipitation. Dry years induced soil moisture recession much earlier in the season in the dense Control stand, and absence of snow eliminated late spring soil moisture replenishment. During above-average precipitation years, soil moisture storage capacity was “topped off” for all treatments, resulting in similar timing of moisture decline across treatments later in the season. Finally, the thinning prescriptions increased soil moisture storage through the height of summer during both drought and wet years. Basal area increment (BAI) increased in the remaining trees, suggesting they used the excess moisture to support rapid growth.